Perlindungan Hukum Hak Konsumen atas Informasi Produk di Marketplace Shopee - Setianingrum, Reni Budi; Nabila Putri, Dhini (Universitas Muhammadiyah Yogyakarta, 2025)
In the Shopee marketplace, numerous sellers offer a wide variety of products. However, the responsibility of business actors to uphold consumer rights remains a persistent issue in consumer services. One of these rights—the right to accurate product information—is stipulated in Article 4(c) of Law Number 8 of 1999 concerning Consumer Protection. This research is a normative legal study that adopts a statutory approach and employs qualitative descriptive analysis. The findings indicate that legal protection for consumers’ rights to product information is clearly regulated by laws and government regulations. If a business actor violates these provisions, they may be subject to sanctions, including trading prohibitions, product withdrawal from circulation, and administrative penalties. Based on customer reviews on Shopee, it is evident that some business operators continue to breach consumers' rights by providing inaccurate or unclear product information. These violations demonstrate that consumers’ rights to accurate product information are not being properly upheld in accordance with the law. Although Shopee has established comprehensive guidelines regarding product descriptions, many sellers still fail to comply with both Shopee’s internal policies and applicable legal regulations, resulting in the continued neglect of consumers’ right to product information.